Analysis of non-alcoholic fatty liver disease during induction therapy for B-cell precursor acute lymphoblastic leukemia in children and adolescents - Hirozumi Sano; Ryoji Kobayashi; Daisuke Suzuki; Masato Yanagi; Daiki Hori; Satoru Matsushima; Kunihiko Kobayashi (Pediatrics and Neonatology)
Background: A prospective evaluation of non-alcoholic fatty liver disease (NAFLD) during induction therapy for acute lymphoblastic leukemia (ALL) has not been performed. Herein, we prospectively investigated the frequency, risk factors, and outcomes of NAFLD during induction therapy in children and adolescents with B-cell precursor ALL (BCP-ALL). Methods: This study enrolled 74 newly diagnosed BCP-ALL cases aged 1 year and older who were admitted to our department between January 2011 and December 2020. Median age was 6.6 years (1.3–17.5 years). Plain computed tomography (CT) of the upper abdomen was performed before induction therapy, and on days 15 and 29 after initiation of induction therapy. Patients with a liver/spleen CT ratio <0.9 were defined as having NAFLD. Results: The frequency of NAFLD was 73%. Patients with NAFLD had a higher rate of hypertriglyceridemia. There was no significant difference in 5-year overall survival and event-free survival (EFS) between patients with and without NAFLD. However, after restricting the target age to 10 years and older, 5-year EFS was significantly higher in patients with NAFLD than in those without (88.5 vs. 42.9%, respectively, P = 0.037). Similarly, 5-year cumulative incidence of relapse (CIR) was significantly lower in patients with NAFLD than in those without it (5-year CIR, 6.3 vs. 57.1%, respectively, P = 0.013). Conclusion: Patients with NAFLD exhibit better outcomes including 5-year EFS and CIR. Further studies are necessary.